Predicciones de precipitación y temperatura del modelo climático global GISS AOM 4x3 para la cuenca hidrográfica del río Portoviejo - Bravo Bermeo, Bernardo Gregorio (2017)
The research consisted in establishing precipitation and temperature predictions through the GISS AOM 4x3 global climate model for the Portoviejo river basin. It addressed four stages: 1) Information analysis of the GISS AOM 4x3 model; where the monthly anomalies of the climatological variables studied were obtained according to the A1B and B1 emission scenarios. 2) Simulation on predictions of climatological variables; these were established in the short, medium and long term (2010-2039, 2040-2069 and 2070-2099 respectively) considering the data established in the register of the actual observed period 1964-2012. 3) Identification of future changes in the basin in the short, medium and long term. 4) Contrast of the results with the weather models GISS AOM 4x3 and HadCM3; a comparison of the results with both models was made to verify the relationship and reliability of the data. Six precipitation predictions and six temperature predictions were obtained (three for each emission scenario), which allowed to identify future changes for the basin in the short, medium and long term. During the period 2010-2039, the lowest level of precipitation (7,185 mm) was recorded in the A1B scenarios, while the temperature in the A1B and B1 scenarios in the three forecast periods is related by a gradual increase; obtaining the greatest increase for the period 2070-2099 up to 2 oC. It was verified that there is no significant variation in the results obtained with the two climatological models, especially in the variable precipitation.